Utopia – więzienie – resocjalizacja. Problem z burzycielami ładu społecznego - Węgrzyn, Rafał; Woźny, Karolina (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2020)
The problem of people violating social order has always existed. The oldest tribes sentenced to exile people who had committed forbidden acts. With the development of civilization and the emergence of codes of law, the ways of administering justice also evolved. Torture, public executions and mutilation turned into imprisonment, i.e. isolation behind the walls of a prison. The awareness of the high level of recidivism gave rise to the need to resocialization the detainees and thus protect the society from their potential criminal acts. However, are contemporary scientific concepts of resoscialization utopian? The main goal of this article is to present several selected utopian concepts of prison in the light of psychology and the resocialization sciences.
Keywords: utopia; resocialization; prison; prisoner; popculture